Eggs, sugar, grated bones: colour-based food preferences in autism, eating disorders, and beyond. Issue 1 (27th April 2020) - Strand, Mattias
Abstract : In 1913, eccentric French composer Erik Satie wrote a fragmentary, diary-like essay where he depicted a strikingly rigid diet consisting solely of white foods: eggs, sugar, coconuts, rice, cream cheese, fuchsia juice and so on. Satie's brief essay has later been used as one of many puzzle pieces in attempts to retrospectively diagnose him with autism spectrum disorder. With Satie's white meal as a starting point, this paper explores colour-based food preferences and selective eating in clinical and non-clinical populations, with a special focus on autism spectrum disorder and avoidant/restrictive food intake disorder (ARFID). General colour preferences and their causes as well as the impact of colour on taste and food identification are also explored. Selective eating during childhood is immensely common and does not generally lead to disordered eating in the long run, although subgroups may experience rigidity around food of a more enduring nature. Problems related to eating were repeatedly described in Kanner's original 1943 autism case series and continue to be common in autism. Most studies on eating and sensory sensitivity in autism show that the texture and consistency of the food are the most common factors behind selective eating. In contrast, colour-based food preferences appear to be relatively rare, although numerous anecdotal reports exist. Foods that are white or colourless may be particularly appealing or tolerable for individuals with sensory hypersensitivity, which can occur in autism or ARFID. Ultimately, in the case of Erik Satie, this paper concludes that his description of a strictly white diet should not be read as an autobiographical account but rather as an ironic take on contemporary symbolist literature, with the famously decadent all-black dinner party in French novelist Joris-Karl Huysmans' À Rebours (1884; also known as Against Nature ) as an obvious source of inspiration.